SYNTHESIS AND CHARACTERIZATION OF TERMOPLASTIC POLY(URETHANE-UREA) VIA PALM OIL EPOXIDATION - MASYKURI (NIM: 30504008), MOHAMMAD
Poly(urethane-urea) is a unique material used in a wide variety of applications such as foams, thermoplastics, elastomers, coatings, and adhesive products. It can be obtained by controlling the functionality, chemical composition, and molecular weight of the different reactants. So far, the raw material of poly(urethane-urea) is petroleum. Unfortunately, the main disadvantage of oil-based poly(urethane-urea) is its high price caused by global energy crisis. In addition, the use of petroleum-based poly(urethane-urea) will increase CO2 production resulting in global warming. Therefore, the investigation of alternative raw materials is absolutely needed. Palm oil as one of the prime indonesian commodities shows a high potential to be developed as raw material of poly(urethane-urea). This study is focused on the synthesis of poly(urethane-urea) from RBDO (refined, bleached and deodorized olein) palm oil by means of epoxidation, oxirane ring-opening, reduction, and polymerization. Oleic acid is used as a model compound for the conversion of palm oil to poly(urethane-urea). The main objective of this study is to investigate the synthesis of poly(urethane-urea) from oleic acid and RBDO and to study its relation with the characteristics of the resulting polymer as a new kind of biopolymers ever synthetized. In the epoxidation stage, the reaction has been optimized using peroxy acids such as peroxyacetic and peroxyformic acids with sulphuric acid as catalyst. In the oxirane ring-opening, three kinds of alcohols, methanol, ethanol, and 1-butanol have been used for nucleophilic addition with p-toluene sulphonic acids (PTSA). The intermediate product of the ring-opening has been reduced by NaBH4 using acid catalyst. The synthesis of poly(urethane-urea) was conducted by using diol compounds from the previous stages, 4,4-methylene bis(phenylisocyanate) (MDI), and two types of chain-extender, ethylene diamine and phenylene diamine, through prepolymer method. The final product of poly(urethane-urea) has been analysed using several techniques, such as determination of chemical structure (FTIR and NMR-1H), intrinsic viscosity, crystallinity (XRD), thermal stability (TG/DTA), surface morphology (SEM), and biodegradability (loss of weight and SEM).